MANAJEMEN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL MELALUI BUDAYA SUNDA DEGUNGAN PADA PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SDN MARGALUYU KECAMATAN CUGENANG - Novi Silvia Mulyani; Cahyanti Yuni Astuti; Mirawati Mirawati; Ricky Yoseptry (Edusaintek)
This study aims to describe the implementation of character education management based on the Sundanese Degungan culture at SDN Margaluyu, Cugenang District. The research uses a qualitative approach with a descriptive method, enabling an in-depth understanding of the planning, implementation, and impact of applying the Sundanese Degungan culture on strengthening students' character. Data were collected through observation, in-depth interviews, and document studies, gathering information from various sources, such as the school principal, teachers, and students. The results show that the application of Sundanese Degungan culture at SDN Margaluyu has a positive impact on strengthening students' character, particularly in the dimensions of gotong royong (mutual cooperation), creativity, and independence. The character education management process involves various parties and is carried out in an environment that supports the formation of character in line with local values. The data were analyzed through data reduction, data presentation, and conclusion drawing to provide an accurate description of the implementation of character education based on local culture at the school